A Survey Study of Veterinary Student Opinions and Knowledge about Pet Reptiles and Their Welfare - Mario Ostović (MDPI AG, 2021)
Exotic pet medicine is rapidly evolving, with reptiles becoming increasingly popular pet animals. Yet, there are only a few literature reports on veterinary perception of reptiles kept as pets. The aim of the study was to assess opinions and knowledge of the Croatian veterinarians-to-be about pet reptiles and their welfare. The questionnaire survey was conducted in the academic year 2019–2020 and included students of all six years of the integrated undergraduate and graduate study at the Faculty of Veterinary Medicine, University of Zagreb. First-year students were surveyed twice, before and after having attended the compulsory course on animal welfare. Questionnaire statements were 5-point Likert scale questions, requiring the students to express their opinions about turtles, lizards and snakes as pets, issues related to their welfare, risks they pose to the health and safety of humans, other animals and the environment, and their self-reported knowledge about pet reptiles. Although expressing higher opinions after having attended the course on animal welfare, first-year student responses remained neutral to most of the statements. Such a trend continued until the end of the study. Student responses revealed that they were uncertain about their knowledge of reptiles as pets, considering different educational areas observed. Study results emphasised the need of alterations in veterinary curriculum and additional student education in reptile medicine. The results obtained have broad implications involving not only the welfare of pet reptiles in clinical practice and elsewhere but also the health and safety of humans and other animals, as well as environmental protection.